Planning Evaluation of Wastewater Treatment System of Jakarta Islamic Hospital Sukapura Kelapa Gading - Yulianto, Udien; Setiawan, Yudi (Westscience Press, 2024)
This study aims to evaluate the effectiveness of the Wastewater Treatment Plant (WWTP) at the Jakarta Islamic Hospital Sukapura Kelapa Gading in meeting government regulations and effluent quality standards. Using evaluation and observation methods, primary and secondary data were collected to analyze the condition of the WWTP, including wastewater quality based on regulated parameters. The results showed that although the WWTP utilizes an anaerobic-aerobic biofilter system, there are still problems in maintenance and inadequate containment capacity. This resulted in the inability of the WWTP to meet quality standards for parameters such as Total Coliform and E.coli. Recommendations for improvement include increasing storage capacity, improving equipment, and increasing maintenance frequency.